RELATIONSHIP BETWEEN VERBAL AND NON-VERBAL COMMUNICATION OF NURSES WITH COMMUNICATION BARRIERS TO FAMILIES OF PRE-SURGERY PATIENTS IN THE INTENSIVE CARE ROOM AT THE ACEH GENERAL HOSPITAL IN 2020 - Hayati, Wirda; Suwarni, Suwarni; Jasna, Nova Riska; Yusuf, Meutia (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: The nurse's verbal and non-verbal communication greatly affects the readiness of the patient and the patient's family to undergo surgery. Unclear communication causes misperceptions and the emergence of communication barriers in the nurse-client interaction process. The limited time and information provided are the causes of communication barriers in the client care process. This of course greatly affects patient care, especially in conditions that require intensive care. Methods: This study aims to determine the relationship between verbal and non-verbal communication between nurses and perceptions of communication barriers in families of pre-surgery patients in the intensive care unit, with a correlation design using a Cross Sectional study approach. The number of samples was 95 families of preoperative patients in the intensive care unit using purposive sampling technique. Results: 51.6% of nurses' verbal communication was good, and 50.5% of nurses' nonverbal communication was good, and there were no communication barriers between nurses and patients' families (54.7%). There was a significant relationship between nurses' verbal communication with perceptions of family communication barriers in pre-surgery patients in the intensive room (P=0.001) and there was a correlation between nurses' nonverbal communication with perceptions of family communication barriers in pre-surgery patients in the intensive room (P=0.002). Recommendation: Nurses are expected to continue to communicate effectively verbal and non-verbal with patients and families to prevent barriers in communication.